188Re-PEI-MP as potential agent for metabolic radiotherapy - Ferreira, Sara (2015)
Introduction: 188Re is a promising radionuclide for metabolic therapy because of the emission of high energy beta-particles. The development of watersoluble bone-seeking polymers such as PEI-MP (polyethyleneimine, functionalised with methylphosphonate-groups) that might be labeled with 188Re are recent approaches, with a strong potential for bone cancer treatment. The aim of this study was to evaluate the efficacy of 188Re-PEI-MP, as therapeutic agent for osteosarcoma, through in vitro and in vivo models.